(untitled) (The Pakistan Development Review, 2025)
“We are short of 10 million housing units” has been the clarion cry in politics, media and the donor-driven research for the last 10 years. Given an average household size of well over six persons, this means that nearly one-third of the population is without housing. Do we see such a huge number of people living on footpaths, side of roads, under bridges or in any open area? Thankfully, NO! We cannot find any clarity on where this huge figure of 10 million housing shortage came from!